IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DALAM BELAJAR BAHASA ARAB KITAB KUNING - Endan Hamdan Ridwan; Gandara, Tedi; Permana, Diansyah (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
Islamic education in Indonesia is an integral part of the Islamic cultural heritage that contributes to the development of national education. One important aspect of Islamic education is learning Arabic through classical texts, commonly known as kitab kuning. These texts play a significant role in Islamic boarding schools (pesantren) and universities, serving as key resources for students in studying Islamic teachings. This study aims to explore effective learning media that can assist students or learners facing difficulties in understanding kitab kuning texts, which are typically written in Arabic and presented in a verbal format. In this context, learning is considered effective when there is a joint commitment and effort between educators and learners. The research method employed is document analysis, focusing on the examination and interpretation of written materials within their context. The analyzed materials include published texts, books, articles, newspapers, magazines, and other relevant documents. The findings indicate that learning Arabic through kitab kuning in Islamic religious education has a positive impact, particularly in enhancing cognitive, affective, and psychomotor knowledge. In conclusion, it contributes to behavioral changes among students or learners, as evidenced by improved teaching and learning quality in both pesantren and universities.